Compounds from culture broth of marine bacterium Oceanisphaera sp - Dao, Phi Thi; Mai Huong, Doan Thi; Murphy, Brian; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Chemistry, 2015)
Eight compounds were isolated and characterized from the culture broth of the marine bacterium Oceanisphaera sp. strain, which was isolated from the sediment collecting at Halong Bay. The structures of all isolates were determined by spectroscopic analysis including MS and 2D NMR, as well as by comparison with reported data in the literature.